Complete unilateral ureteral duplication encountered during intersphincteric resection for low rectal cancer. Issue 10 (11th October 2018) - Varlatzidou, Alexandra; Zarokosta, Maria; Nikou, Euthumios; Theodoropoulos, Panagiotis; Kakaviatos, Dimosthenis; Piperos, Τheodoros; Kalles, Vasileios; Bonatsos, Vasileios; Mariolis-Sapsakos, Theodoros
Abstract: Complete duplication of ureters is a very rare clinical entity that may either be asymptomatic or present with a variety of clinical findings. In the presented case a 51-year-old Caucasian female underwent an intersphincteric resection for low rectal cancer. Intraoperatively, during the standard bilateral recognition and mobilization of the ureters, complete unilateral duplication of the left ureter was incidentally detected, deriving from a single renal parenchyma. Such a congenital abnormality though constitutes a major risk-factor of accidental ureteral injury during operations including pelvis. Conclusively, meticulous exposure of both ureters combined with surgeons' unceasing awareness constitute the cornerstone of a safe operation.